An Analysis of EFL Learners' Vocabulary and Lexical Collocational Knowledge - Ardi Nugroho (Universitas Bunda Mulia, 2018)
One of the problems that EFL learners, more specifically Indonesian learners of English, often face deals with collocation. A possible reason for why learners often make inaccurate collocations is the influence of the learners’ L1 or mother tongue. Another likely reason for the learners’ inability to produce native-like collocations is their lack of vocabulary knowledge. So how exactly does one measure learners’ vocabulary knowledge? One way of doing it is by looking at their vocabulary size and depth as well as their receptive and productive vocabulary. From this, the writer has become interested in exploring the relationship between learners’ vocabulary and collocational knowledge, as well as the learners’ L1 influence on their collocation recognition and production. The source of data for the current research is students from the second and fourth semesters of the English Language and Culture department at Bunda Mulia University. In order to measure these variables, the following tools are used: the Vocabulary Size Test (Nation and Beglar, 2007), the Words Associate Test (Read, 1998) and an adapted version of Gyllstad’s (2007) receptive and Nikonzika’s (2012) productive collocation tests. Each of the variables is analyzed using the Pearson product-moment correlation. The findings show that there is a significant positive correlation between the students’ vocabulary knowledge and English lexical collocational knowledge. It is also found that the students’ L1 directly influences their recognition and production of English lexical collocations. Keywords: vocabulary size and depth, receptive and productive collocation